EXPLORING EU STUDENTS’ BELIEFS AND EXPOSURE TO SEXUAL HARASSMENT AND SEXUAL ASSAULT - Ahrens, Andreas; Zascerinska, Jelena; Zascerinskis, Mihails; Bikova, Anastasija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Sexual harassment and assault are the factors that decrease youth quality employment. The research aim is to explore students’ beliefs and exposure to sexual harassment and sexual assault in selected countries of the European Union underpinning the elaboration of implications for higher education. Theoretical analysis and modelling were used. The exploratory study was implemented to investigate the relationship between students’ self-assessment of their beliefs and levels of exposure in relation to sexual harassment and sexual assault in the selected countries of the European Union. The theoretical analysis resulted in the establishment of the inter-connections between sexual harassment and sexual assault, on the one side, and students’ employment and work/job, health as well as non-direct economic impact, on the other side. The exploratory study revealed that the level of students’ belief is higher if compared to the level of exposure to sexual harassment and assault. Students most believe that people physical appearance, race and being young impact sexual harassment and sexual assault. Exposure to sexual harassment and sexual assault coincide in relation witnessed sexual harassment and sexual witnessed assault as well as their ranking. Implications for higher education refer to teaching staff in higher education. Further research directions were proposed.